Factors determining quality of life of patients with ischemic cardiomyopathy selected for revascularization procedures - N.B. Іvaniuk; О.J. Zharinov; K.O. Mikhaliev; О.А. Yepanchintseva; B.М. Тоdurov (Кардіохірургія та інтервенційна кардіологія)
The aim – to evaluate the determinants of quality of life (QoL) of patients with ischemic cardiomyopathy selected for coronary artery bypass grafting or coronary stenting. Materials and methods. The cross-sectional single-center study analyzed data obtained at clinical and instrumental examination of 148 consecutively admitted patients with ischemic cardiomyopathy, including 130 men and 18 women, mean age 62 ± 9 years. Demographic characteristics, risk factors, concomitant diseases and background treatment were analyzed. QoL indicators were assessed by SAQ questionnaire and compared with those in other studies performed in heart failure patients. Results. The key features of the surveyed cohort of patients that might explain poor QoL were high frequency of previous myocardial infarction and presence of left ventricular systolic dysfunction. In addition, the patients studied were younger, were characterized by lower incidence of three-vessel coronary artery disease and diabetes mellitus. Conclusions. Improvement of ischemic cardiomyopathy and of the QoL changes is one the main arguments in favor of surgical or endovascular revascularization.